A Straightforward Treatment of Activity in Aqueous CaCO3 Solutions and the Consequences for Nucleation Theory. (5th December 2013) - Kellermeier, Matthias; Picker, Andreas; Kempter, Andreas; Cölfen, Helmut; Gebauer, Denis
<x xml:space="preserve">Abstract</x> The aqueous calcium carbonate system is rigorously investigated with respect to ionic activity. Ideal treatment is found to be a good approximation at relevant concentrations. The data further show that bound CaCO3 species cannot be regarded as "inactive" during nucleation but rather appear to play a key role in the phase‐separation process, and that amorphous calcium carbonate (ACC) can be precipitated from much lower levels of supersaturation than previously believed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>